Achieving a dream in the agricultural sector - Herz Ghersi, Jeannette M. (2019)
Mike Arce is the owner of a 30-hectare farm in an agricultural area on the coast north of Lima, Peru. He must find a solution to the liquidity problem that arose at the end of 2016 and determine if he has adequate accounting information to make his decision. Students are challenged to review information from an accounting and financial perspective. In the resolution of the case, international rules concerning information to be submitted via financial statements must be considered, especially taking into account the rules concerning agriculture, property/plant and equipment and inventories. This case lends itself to analysis and projection of financial statements and to seeking alternative solutions.